Development of mobile control system for lighting tower in golf courses - Ho Kim, Yong; IL Chang, Hui (International Journal of Engineering and Technology, 2018)
Background/Objectives: It is a common for existing golf courses to manage all lighting facilities in batches because it is hard to controllighting individually. That is very much part of the golf courses and forces the whole golf course to light on even though play was finished due to the difficulty of real time checking situationMethods/Statistical analysis: Lighting control device and method in this study are provided not only to control remotely individual lighting installed each hole in golf course but to inspect failure of lighting. There is no longer to stay golf course in person to control lighting system.Findings:Lighting control device and method to be able to control individual lighting installed each hole in golf course is provided to response for the problem in a waste of electricity after playing. User device makes it possible to remotely control lighting and inspect failure of itImprovements/Applications: It can expect to reduce golf course operation management cost by building a smart tower remote control systemÂ Â